2008
DOI: 10.1007/s00442-008-1160-5
|View full text |Cite
|
Sign up to set email alerts
|

Species effects on ecosystem processes are modified by faunal responses to habitat composition

Abstract: Heterogeneity is a well-recognized feature of natural environments, and the spatial distribution and movement of individual species is primarily driven by resource requirements. In laboratory experiments designed to explore how different species drive ecosystem processes, such as nutrient release, habitat heterogeneity is often seen as something which must be rigorously controlled for. Most small experimental systems are therefore spatially homogeneous, and the link between environmental heterogeneity and its … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
53
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 56 publications
(59 citation statements)
references
References 44 publications
6
53
0
Order By: Relevance
“…In the present study, E. atakama spent 150 min relocating and 267 min feeding (a ratio of 1:1.8), suggesting that resource supply is indeed abundant and that the distance between patches is relatively short (20-40 min travel time, or approximately 10 body length distance). This pattern of movement suggests considerable sensitivity to food concentration (McClintic et al 2008) and implies that the dynamics and organisation of hadal communities are intimately linked to habitat structure and the distribution of resources in ways similar to those found in shallower benthic communities (Levinton and Kelaher 2004;Dyson et al 2007;Bulling et al 2008;Nogaro et al 2008;Godbold et al 2011). Thus, the cumulative response of hadal species to such small-scale variation is likely to influence species contributions to ecosystem properties at much larger scales (Godbold et al 2011).…”
Section: Discussionmentioning
confidence: 86%
“…In the present study, E. atakama spent 150 min relocating and 267 min feeding (a ratio of 1:1.8), suggesting that resource supply is indeed abundant and that the distance between patches is relatively short (20-40 min travel time, or approximately 10 body length distance). This pattern of movement suggests considerable sensitivity to food concentration (McClintic et al 2008) and implies that the dynamics and organisation of hadal communities are intimately linked to habitat structure and the distribution of resources in ways similar to those found in shallower benthic communities (Levinton and Kelaher 2004;Dyson et al 2007;Bulling et al 2008;Nogaro et al 2008;Godbold et al 2011). Thus, the cumulative response of hadal species to such small-scale variation is likely to influence species contributions to ecosystem properties at much larger scales (Godbold et al 2011).…”
Section: Discussionmentioning
confidence: 86%
“…To incorporate habitat heterogeneity, patches were either non-enriched (NE) or enriched (E) with dried, ground U. intestinalis [18,19]. We assembled two heterogeneity configurations (H A and H B ).…”
Section: Methodsmentioning
confidence: 99%
“…[17,18,44]). As a first step, a linear regression model was applied to check that underlying statistical assumptions were not violated.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Natural environments tend to be heterogeneous, whereas mesocosm or laboratory studies are generally controlled homogeneous environments (Dyson et al 2007). Natural heterogeneity has been observed to buffer against stressor effects (Godbold et al 2011) or negate patterns observed under laboratory conditions (Bulling et al 2008).…”
Section: Field Experimentationmentioning
confidence: 99%